1993
DOI: 10.1073/pnas.90.17.8136
|View full text |Cite
|
Sign up to set email alerts
|

Bilitranslocase and sulfobromophthalein/bilirubin-binding protein are both involved in the hepatic uptake of organic anions.

Abstract: The hepatic uptake of cholephiic organic anions is a carrier-mediated process. Three distinct proteins [bilitranslocase (BTL), sulfobromophthalein (BSP)/bilirubinbinding protein (BBBP), and organic anion-binding protein] have been isolated from the basolateral plasma-membrane domain of the hepatocyte. To investigate the relative role of the first two of them in accounting for the hepatic uptake oforganic anions, we measured the initial rates of uptake of 35S-labeled BSP into rat liver plasma-membrane vesicles.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…In a comparative study, Claudio Tiribelli's group has shown that uptake of bilirubin by bilitranslocase is electrogenic whereas such uptake by the BSP/ bilirubin-binding protein is electroneutral. These authors concluded that the two proteins operate in parallel, where the relative role of each on the overall transport depends on substrate concentration (95).…”
Section: Transport Of Bilirubinmentioning
confidence: 99%
“…In a comparative study, Claudio Tiribelli's group has shown that uptake of bilirubin by bilitranslocase is electrogenic whereas such uptake by the BSP/ bilirubin-binding protein is electroneutral. These authors concluded that the two proteins operate in parallel, where the relative role of each on the overall transport depends on substrate concentration (95).…”
Section: Transport Of Bilirubinmentioning
confidence: 99%
“…BSP/Bilirubin binding protein (BBBP) is a protein isolated from rat liver located on the sinusoidal membrane of the liver and described as a transport protein involved in the well known sodium-independent hepatic uptake of BSP and bilirubin (Stremmel & Berk, 1986;Stremmel et al, 1986;Torres et al, 1993;Torres, 1997). The transport of this protein is electroneutral as indicated by experiments in liver plasma membrane vesicles.…”
Section: Bbbpmentioning
confidence: 99%
“…92 Despite these uncertainties about the involved carrier proteins, the observations of low and high affinity bile salts and the nonbile salt organic anion BSP. 7,8,12,15,83 Furthermore, competitive interactions with hepatocellular BSP uptake systems 34,89,90,[93][94][95][96][97][98][99][100] (Table 1) with different potential dependencies, 89 distinct cellular distribution, 101 dif-Na / -independent bile salt uptake has also been observed for cardiac glycosides and other neutral steroids, 7,8,11,13,84,85 vari-ferential modulation by sex steroids, 98 and selective inducibility by phenobarbital 6,90 clearly indicate that more than ous linear and cyclic peptides, 7,8,10,45,66,86,87 certain organic cations, 13,14 and numerous other drugs and toxins. 7,8,16,17,88 one sinusoidal BSP/bilirubin uptake systems are present in rat hepatocytes.…”
mentioning
confidence: 99%